Growth of Date Palm (Phoenix dactylifera L.) in Composts of Olive Oil Mill Waste with Organic Household Refuse. Issue 4 (1st October 2016) - Barje, Farid; Meddich, Abdelilah; El Hajjouji, Houda; El Asli, Abdelghani; Ait Baddi, Ghita; El Faiz, Abdelouahed; Hafidi, Mohamed
ABSTRACT: This study highlights the effects of composts of olive mill wastes and organic household refuse with a pH range of 7 to 7.98 and a C/N ratio between 14.9 and 22, to improve the growth and the mineral nutrition of the date palm ( Phoenix dactylifera L.). After 7 months of cultivation, plants amended with composts showed higher biomass production than the controls. Compost C1, i.e., the basic compost with no additives phosphate, at 100% and 45% doubled the production of dry matter in comparison with control plants. The rise of root biomass was considerably greater for plants grown with compost C1 without phosphate. In contrast, the shoot biomass was highly significant for composts C2 and C3 enriched with phosphate. The control plants, grown without amendment, showed significantly higher specific root length (SRL) and specific leaf length (SLL). The efficiency of compost application was reflected by the biomass rise, the number of emerged leaves (2.6–4), and the rise in leaf area (3.3 to 6.7 cm 2 ) by improving the mineral nutrition of the date palm. The composts of olive mill waste and organic household refuse supplemented with natural rock phosphate, or not, generated a notable agronomic added value.